2017
DOI: 10.1007/s00284-017-1196-z
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Methicillin-Resistant Staphylococcus aureus (MRSA) and Acanthamoeba polyphaga

Abstract: The interactions that occur between bacteria and amoebae can give through mutual relations, where both organisms benefit from the association or parasitic in which one organism benefits at the expense of the other. When these organisms share the same environment, it can result in some changes in the growth of organisms, in adaptation patterns, in morphology, development or even in their ability to synthesize proteins and other substances. In this study, the interaction between Acanthamoeba polyphaga and Staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Furthermore, it was shown that the conditioned media from Acanthamoeba culture possess bactericidal activities against selected bacteria, since the medium eliminated all methicillin-resistant Staphylococcus aureus whilst showing limited effects against Acinetobacter sp., vancomycin-resistant Enterococcus faecalis and Pseudomonas aeruginosa (Iqbal et al 2014 ). Also, it was recently reported that Acanthamoeba produces a metabolite that inhibits the growth of methicillin-resistant Staphylococcus aureus (de Souza et al 2017 ). Interestingly, it has been shown that Acanthamoeba may interfere with bacterial toxin production, such as 2,4-diacetylphloroglucinol and monoacetyl–phloroglucinol in Pseudomonas fluorescens (Jousset and Bonkowski 2010 ), which may enhance its predatorial capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that the conditioned media from Acanthamoeba culture possess bactericidal activities against selected bacteria, since the medium eliminated all methicillin-resistant Staphylococcus aureus whilst showing limited effects against Acinetobacter sp., vancomycin-resistant Enterococcus faecalis and Pseudomonas aeruginosa (Iqbal et al 2014 ). Also, it was recently reported that Acanthamoeba produces a metabolite that inhibits the growth of methicillin-resistant Staphylococcus aureus (de Souza et al 2017 ). Interestingly, it has been shown that Acanthamoeba may interfere with bacterial toxin production, such as 2,4-diacetylphloroglucinol and monoacetyl–phloroglucinol in Pseudomonas fluorescens (Jousset and Bonkowski 2010 ), which may enhance its predatorial capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Amoebae resistant bacteria (ARB) are able to resist death by phagocytosis and benefit from interactions with FLA. There is a wide diversity of these ARB; however, some of these bacteria have been described as human pathogens, such as Staphylococcus aureus, Listeria monocytogenes, Salmonella spp., Vibrio cholerae, Helicobacter pylori, Legionella pneumophila, Mycobacterium avium, or Pseudomonas aeruginosa [35][36][37][38]. Mounting evidence suggests that FLA increase both the number and virulence of intracellular bacteria, allowing for increased rates of infectivity and intracellular replication [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Using that media, Fieseler and colleagues (2014) also demonstrated that the growth of Listeria monocytogenes was promoted by A. castellanii supernatant thanks to its ability to use compounds secreted by amoebae. On the contrary, A. polyphaga filtered supernatant realized in PBS led to a reduction of the growth of S. aureus MRSA suggesting that the amoebae could secrete compounds with antibacterial activity (de Souza et al ., 2017). These data illustrated that in a minimal medium, some amoebal compounds can alter the growth of bacteria but that these modifications differed according to bacterial genera and/or amoebal species.…”
Section: Discussionmentioning
confidence: 99%